Xin-Ji-Er-Kang protects heart from ischemia-reperfusion injury by rebalancing lipid metabolism - Sun, Li-Jun; Wang, Xiao-Yu; Xia, Jie; Xu, Yan-Mei; Liao, Yu-Feng; Qin, Yuan-Yuan; Ge, Xue-Wan; Zhao, Pei-Wen; Xu, Tong; Zhu, Xiao-Ling; Gao, Shan; Xiao, Rui; et al. (Frontiers in Pharmacology, 2022)
Background and Purpose: We have previously reported a cardioprotective effect with Xin-Ji-Er-Kang (XJEK) treatment in mice with myocardial infarction (MI)-induced heart failure, but no report about its potential functions in myocardial ischemia-reperfusion (MIR) injury. Here we studied the therapeutic effects of XJEK on MIR injury and investigated the mechanisms involved. Experimental Approach: MIR model of Balb/c mice induced by left anterior descending coronary artery ligation for half an hour, followed by reperfusion, was utilized to study the potential therapeutic effects of XJEK on MIR-induced cardiac injury. Ultra-performance liquid chromatography tandem Orbitrap mass spectrometry platform was used for studying serum lipid metabolic signatures. Key Results: MIR caused cardiac dysfunctions, cardiac injury, myocardial fibrosis, and increased inflammation, and all the observed abnormalities caused by MIR were largely corrected by XJEK treatment. Mechanistically, XJEK exerts its cardioprotective effect in the context of MIR injury by suppressing MIR-induced inflammation and dysregulation of serum lipid metabolism. Conclusion and Implications: We have demonstrated for the first time that XJEK protects heart from MIR injury by restoring dysregulated lipidomics. Our data provide new evidence to support a therapeutic effect for XIEK on MIR-induced cardiac injury, and pave the way for exploring the therapeutic potential of XJEK in large animal study and early clinical trial.